2018
DOI: 10.1007/s10544-018-0262-z
|View full text |Cite
|
Sign up to set email alerts
|

Finite element analysis of hollow out-of-plane HfO2 microneedles for transdermal drug delivery applications

Abstract: Transdermal drug delivery (TDD) based on microneedles is an excellent approach due to its advantages of both traditional transdermal patch and hypodermic syringes. In this paper, the fabrication method of hollow out-of-layer hafnium oxide (HfO) microneedles mainly based on deep reactive ion etching of silicon and atomic layer deposition of HfO is described, and the finite element analysis of the microneedles based on ANSYS software is also presented. The fabrication process is simplified by using a single mask… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…The “bed-of-nails” effect has been explained more recently using the finite element analysis of a 3 × 3 hafnium oxide MN array [ 150 ]. Reducing the spacing between individual MNs (from 80 to 20 µm) resulted in smaller MN maximal height difference (i.e., the difference in MN height after application to the skin when compared to the original MN height before application to the skin), which caused a reduced maximal stress in skin.…”
Section: Parameters Affecting Mn Insertionmentioning
confidence: 99%
See 1 more Smart Citation
“…The “bed-of-nails” effect has been explained more recently using the finite element analysis of a 3 × 3 hafnium oxide MN array [ 150 ]. Reducing the spacing between individual MNs (from 80 to 20 µm) resulted in smaller MN maximal height difference (i.e., the difference in MN height after application to the skin when compared to the original MN height before application to the skin), which caused a reduced maximal stress in skin.…”
Section: Parameters Affecting Mn Insertionmentioning
confidence: 99%
“…Reducing the spacing between individual MNs (from 80 to 20 µm) resulted in smaller MN maximal height difference (i.e., the difference in MN height after application to the skin when compared to the original MN height before application to the skin), which caused a reduced maximal stress in skin. Thus, when the same pressure was applied to the MNs of different spacing, the skin was not pierced when the MN spacing decreased to 20 µm [ 150 ].…”
Section: Parameters Affecting Mn Insertionmentioning
confidence: 99%
“…An MTT assay was conducted for evaluating the cytotoxicity of PDA/LA-HMSN. 7 Various PDA/LA-HMSN concentrations (12,25,50, 100, and 200 μg/mL) were incubated with 3T3-L1 cells in a 96-well plate in a CO 2 humidified incubator (5%, 37 °C) for 48 h. Another incubation of 4 h was performed after an MTT solution (20 μL, 5 mg/mL) was added into wells. Afterward, DMSO (150 μL) was added to wells with a removal of MTT solution from each well.…”
Section: Introductionmentioning
confidence: 99%
“…These microchannels can allow the drug to penetrate or cross the skin epidermis into the system’s circulation. Therefore, it is a more effective and attractive method for drug delivery with high compliance for patients. …”
Section: Introductionmentioning
confidence: 99%
“…One of these studies described the fabrication and analysis of hollow and tubular hafnium oxide MN. Their fabrication was based on deep reactive ion etching and atomic layer deposition, and required only one mask (Zhang et al, 2018a). This study mainly analyzed MNs flexibility and concluded that this feature could be tuned depending on the required application.…”
Section: Needle-based Transdermal Drug Delivery Devicesmentioning
confidence: 99%